2004
DOI: 10.1093/humrep/deh420
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone does not induce cervical softening in non-pregnant women

Abstract: Unlike its dramatic effect in the pregnant uterus, mifepristone administered 30 h prior to hysteroscopy was not effective in ripening the cervix of non-pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
0
21
0
2
Order By: Relevance
“…Although the use of saline solution as distension medium has been preferred to carbon dioxide by some authors (8,9), other authors (10,11) observed similar discomfort with the use of one or the other. Misoprostol and mifepristone are effective in cervical ripening, but their use causes more severe pain and discomfort, without any advantage in terms of quality of visualization (12)(13)(14).…”
mentioning
confidence: 99%
“…Although the use of saline solution as distension medium has been preferred to carbon dioxide by some authors (8,9), other authors (10,11) observed similar discomfort with the use of one or the other. Misoprostol and mifepristone are effective in cervical ripening, but their use causes more severe pain and discomfort, without any advantage in terms of quality of visualization (12)(13)(14).…”
mentioning
confidence: 99%
“…Six studies were considered eligible for inclusion in the review (Figure 1). 11–16 The inter‐rater reliability for the study selection was very good (κ = 0.86). Four of the six papers were deemed to be of high quality 12,13,15,16 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…An attempt was made to contact authors for their primary data but unfortunately insufficient data were received to be able to perform any analysis. The incidence of gastrointestinal adverse effects were reported by two studies, 15,16 bleeding by four studies, 11,14–16 cervical lacerations by three studies 11,13,16 and failed procedures by three studies 12,13,15 . These results were meta‐analysed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although misoprostol has been demonstrated to cause cervical ripening and dilation in the pregnant patient, 19 results with the same medication in similar doses and administration times in the nonpregnant patient are conflicting. 23,24 Few studies have investigated the use of cervical priming agents in office hysteroscopy alone. The first received 400 g of misoprostol vaginally 4 to 6 hours before the procedure, and the control group received nothing.…”
Section: Cervical Primingmentioning
confidence: 99%